Avaliação da atividade inseticida de novos derivados de neonicotinóides em Anopheles darling Root, 1926 (Diptera: Culicidae) - Mesquita, Rochelly da Silva (2012)
Amongst malaria control strategies, the use of chemical insecticides constitutes, so far, one of the most utilized methods for fighting its vector. Insect control methods call for a larger number of biological active substances for being utilized as feasible alternatives, as associated to other control procedures. The present work undertook the synthesis of new insecticide activity bearing substances derived from neonicotinoids, a new class of chemical insecticides. Compound synthesis responses occurred through addition, reduction and nitration reactions. Products were characterized according to their melting point, infrared spectroscopy, mass spectroscopy, RMN of 1H and 13C. So as to evaluate the insecticidal activity of synthesized compounds and imidacloprid (Provado® - neonicotinoid commercial product), selective and dose bioassays were carried out with A. darlingi larvae for assessing compound toxicity and subsequent calculation of the CL50, through the use of the POLO-PC® software. The toxicity against adult mosquitoes was evaluated by means of bottle biological proofs. Using data acquired through spectrophotometry, three compounds were suggested: 3- piridinecarboxilic acid 6-chloro 2-hidrazine carbotioamide, 3-hidroxipiridine 6-chloro 2- hydrazine aminetiomethyl and possible isomers of 5-nitrobenzoil 3- piridinacarboxilic acid 6-chloro 2-carbotioamide hydrazine. Amongst these, only 3- piridinacarboxilic acid 6-chloro 2-carbotioamide hydrazine failed to present larvicidal activity in the selective bioassays. Dose bioassays for synthesized compounds as well as imidacloprid presented non-significant χ2 values, indicating that data adjusted itself to the probit model, within the reading gaps. The CL50 values showed to be 503 ppm and 0.17 ppm for compound 2 and imidacloprid, respectively, following 24 h of exposure. Bottle biological proof tests detected no mosquito mortality for the synthesized products. Therefore, different structural modifications of the molecule derived from neonicotinoids showed the synthesized products low insecticidal efficiency, which may be related the molecule’s substituting radicals that contributed for altering the biological activity, when compared to the commercial compound, imidacloprid. Keywords: neonicotinoids, larvicidal activity, Anopheles darlingi, compounds synthesis, imidacloprid.